ASPEK PENDIDIKAN RUHIYAH DALAM AL QURAN - Kholil, Munawar (Jurnal Pendidikan Guru, 2017)
God provides a set of basic capabilities that have a tendency to grow, which in the so-called potential or known psychological disposition, which, according to the flow of so-called psychological behaviorism prepoten reflexi (basic capability that can automatically grow). Humans have three potential in him, namely, the potential of a body, mind and spirit. Each potential intake must be provided. Human advantage lies in the best possible shape creature (Ahsana al Taqwim) in its beauty, perfection in shape, as well as the ability to interpret, both intellectual and spiritual. This paper tries to explore the meaning Taqwim intended by the Qirâan, especially associated with the potential to be developed in the eduaction of the present and the future.